IoT sensing technology based on acoustic phase - Yang LIU; Wuxiong ZHANG; Weidong FANG (物联网学报, 2018)
The perception and interaction technology between IoT devices is one of the necessary foundations for the development of the Internet of things.With the growing popularity of multimedia devices,such as smart phones,tablet,and home audio,the speakers and microphones are ubiquitous on these devices which make it possible to the low cost interaction between devices using acoustic signal.The low speed and low frequency physical properties of sound waves make the acoustic-based sensing technology have higher accuracy and lower computation.A phase based measurement method using acoustic signals was proposed,which could be used to measure high precision distance between different mobile devices and sound sources.In a certain range,firstly,the mobile device receives the single frequency acoustic signal transmitted by a sound source.The mobile device uses the sound signal to synchronize the phase between the mobile devices the sound source,and then calculates the distance between the mobile device and the sound source by calculating the phase difference during movement.